2012
DOI: 10.2119/molmed.2011.00281
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the B-Cell Compartment Favors Operational Tolerance in Human Renal Transplantation

Abstract: Transplanted individuals in operational tolerance (OT) maintain long-term stable graft function after completely stopping immunosuppression. Understanding the mechanisms involved in OT can provide valuable information about pathways to human transplantation tolerance. Here we report that operationally tolerant individuals display quantitative and functional preservation of the B-cell compartment in renal transplantation. OT exhibited normal numbers of circulating total B cells, naive, memory and regulatory B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
71
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 54 publications
7
71
0
4
Order By: Relevance
“…Simultaneously, a high BAFF or BAFFR level is associated with a higher risk of Ab production in stable patients, Ab‐mediated rejection, and graft dysfunction . In humans, BAFF blockade using belimumab, a human monoclonal Ab against BAFF, has been shown to be effective in the treatment of systemic lupus erythematosus . Considering that B cell survival, proliferation, and maturation are strongly induced by BAFF, it may be critical to reduce BAFF levels in the peripheral blood by a combination therapy with anti‐BAFF monoclonal Ab to enable the full efficacy of alemtuzumab during organ transplantation …”
Section: Regulatory Functions Of B Cells In Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneously, a high BAFF or BAFFR level is associated with a higher risk of Ab production in stable patients, Ab‐mediated rejection, and graft dysfunction . In humans, BAFF blockade using belimumab, a human monoclonal Ab against BAFF, has been shown to be effective in the treatment of systemic lupus erythematosus . Considering that B cell survival, proliferation, and maturation are strongly induced by BAFF, it may be critical to reduce BAFF levels in the peripheral blood by a combination therapy with anti‐BAFF monoclonal Ab to enable the full efficacy of alemtuzumab during organ transplantation …”
Section: Regulatory Functions Of B Cells In Transplantationmentioning
confidence: 99%
“…In 2010, the tolerance‐associated gene signature in 25 renal transplant recipients with operational tolerance (long‐term graft survivors after immunosuppressive drug withdrawal) was found to be rich in B cell‐related genes . In 2012, normal preservation of the B cell compartment was found in renal transplant recipients of the operational tolerance group (OTG) . In 2014, B cells in patients with operational tolerance were found to exhibit normal proliferation but produce higher levels of IL‐10 than those in immunosuppressive drug‐treated patients with stable graft function .…”
Section: Regulatory Functions Of B Cells In Transplantationmentioning
confidence: 99%
“…An additional explanation may be that Breg are also depleted by the treatment, thus hampering their tolerogenic function. In this sense, some studies have shown that preserving the B cell compartment favors OT in renal transplantation [41]. …”
Section: Potential Role Of Regulatory B Cells In Transplantationmentioning
confidence: 99%
“…These studies implicated Bregs (B regulatory cells) as the basis of increased numbers of B cells in tolerant patients with kidney transplantation. [39][40][41] Independent of the complexity and novelty of the method used, it is important to take into account a number of confounding variables, both clinical and demographic, when evaluating diagnostic or predictive biomarkers. We are using a very potent technology in poorly designed clinical trials.…”
Section: Regulatory T Cells As Biomarkers In Solid Organ Transplantationmentioning
confidence: 99%